2018
DOI: 10.1007/s10900-018-0519-8
|View full text |Cite
|
Sign up to set email alerts
|

Hookah Use Among College Students: Recent Use, Knowledge of Health Risks, Attitude and Reasons for Use

Abstract: Notwithstanding the efforts of health educators and other health professionals regarding tobacco and smoking cessation, research indicates that hookah smoking among college students remains a health concern. Research shows an upward trend in college students' hookah use. The purpose of this study was to identify and describe potential patterns/differences in college students' hookah use, and the relations among attitudes toward and knowledge about hookah use and use of this drug. A four-page, 20-item survey wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 39 publications
2
6
0
1
Order By: Relevance
“…Other studies also confi rm that hookah smoking is mainly associated to the population of students in colleges and universities (Krenik-Matejcek et al, 2017;Awan et al, 2017), as around 32% of students reported on smoking, with a similar rate found between male and female students (33% and 34%, respectively) ( Krenik-Matejcek et al, 2017;Fevrier et al, 2018). In addition, fi ndings from the research of Salloum et al (2017) that reported on hookah usage rates in all demographic segments among young adults (18)(19)(20)(21)(22)(23)(24), show that the rates of hookah smoking were lower among M.A.…”
Section: Socio-demographic Characteristics Associated To Hookah Smokingmentioning
confidence: 84%
“…Other studies also confi rm that hookah smoking is mainly associated to the population of students in colleges and universities (Krenik-Matejcek et al, 2017;Awan et al, 2017), as around 32% of students reported on smoking, with a similar rate found between male and female students (33% and 34%, respectively) ( Krenik-Matejcek et al, 2017;Fevrier et al, 2018). In addition, fi ndings from the research of Salloum et al (2017) that reported on hookah usage rates in all demographic segments among young adults (18)(19)(20)(21)(22)(23)(24), show that the rates of hookah smoking were lower among M.A.…”
Section: Socio-demographic Characteristics Associated To Hookah Smokingmentioning
confidence: 84%
“…Na realidade brasileira, em uma pesquisa que comparou estudantes que não tinham o hábito de beber excessivamente com aqueles que o tinham, estes apresentaram maiores escores em testes que identificam transtornos relacionados ao álcool, além de apresentarem percepção reduzida a respeito da negatividade das consequências, apesar destas estarem presentes (Bedendo, Andrade, Opaleye & Noto, 2017). De modo semelhante, há estudos que evidenciam a existência de uma percepção, por parte dos estudantes universitários, de baixo risco em relação ao hábito de fumar narguilé e apontam para a importân-cia da prevenção ao uso (Fevrier, Nabors, Vidourek & King, 2018).…”
Section: B) a Percepção E O Conhecimento Em Relação Aos Riscos E Comounclassified
“…[17] A recent study from the United States found that college students have low negative perceptions of the health risks (addictive and detrimental properties) of hookah use. [18] A very recent systematic review that addressed the knowledge, attitudes, and perceptions toward water pipe tobacco smoking among college or university students found several reasons for initiation of water pipe smoking among this group, including curiosity, peer/social influence, wanting to overcome the social anxiety, a belief that water pipe smoking is popular among peers or is a socially acceptable form of tobacco smoking that retains a certain prestige, and the belief that it is more socially acceptable than cigarettes. Among the most common reasons associated with continued water pipe smoking were the opportunity to socialize; the opportunity to be fun, pleasurable, attractive, and relaxing; media portrayal; and the belief that water pipe smoking is less harmful than cigarette smoking.…”
Section: Rising Prevalence Of Water Pipe Smokingmentioning
confidence: 99%